2022
DOI: 10.1039/d2tc02717h
|View full text |Cite
|
Sign up to set email alerts
|

A temperature-dependent tricoloured mechanochromic fluorescence material with polymorphic structures

Abstract: High-contrast mechanochromic fluorescent materials are highly appealing due to their potential applications in security, anti-counterfeiting and memory. Considering that polymorphic molecules usually exhibit reversible mechanochromism, we adopted Polymorph Prediction to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…This heightened ICT effectively suppresses the occurrence of the ESIPT process . By comparing the fluorescence spectra of the crystal at room temperature and 77 K, it was found that a distinct shoulder peak around 460 nm related to the vibrational structure of compound 1 was observed at 77 K. The blue shift of the fluorescence at 77 K may be attributed to the rotation of the molecule that is suppressed in the crystalline state at low temperature, resulting in more expression of the LE emission. …”
Section: Resultsmentioning
confidence: 94%
“…This heightened ICT effectively suppresses the occurrence of the ESIPT process . By comparing the fluorescence spectra of the crystal at room temperature and 77 K, it was found that a distinct shoulder peak around 460 nm related to the vibrational structure of compound 1 was observed at 77 K. The blue shift of the fluorescence at 77 K may be attributed to the rotation of the molecule that is suppressed in the crystalline state at low temperature, resulting in more expression of the LE emission. …”
Section: Resultsmentioning
confidence: 94%